2018
DOI: 10.1038/s41431-018-0222-3
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of three ciliopathy pedigrees expands the phenotype associated with biallelic C2CD3 variants

Abstract: Whole exome sequencing (WES) is utilized in diagnostic odyssey cases to identify the underlying genetic cause associated with complex phenotypes. Recent publications suggest that WES reveals the genetic cause in ~25% of these cases and is most successful when applied to children with neurological disease. The residual 75% of cases remain genetically elusive until more information becomes available in the literature or functional studies are pursued. WES performed on three families with presumed ciliopathy diag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 30 publications
0
16
0
Order By: Relevance
“…Finally, recent reports showed that mutations in the C2CD3 gene cause skeletal dysplasia, polydactyly, and ciliopathies 50,51 , while Talpid3 mutations cause Joubert syndromes and Short-Rib polydactyly syndromes 52,53 . We herein showed that CEP120 directly interacts with C2CD3 (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, recent reports showed that mutations in the C2CD3 gene cause skeletal dysplasia, polydactyly, and ciliopathies 50,51 , while Talpid3 mutations cause Joubert syndromes and Short-Rib polydactyly syndromes 52,53 . We herein showed that CEP120 directly interacts with C2CD3 (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The ta 3 has a more severe DV patterning defect (a complete loss of ventral cell types) in the neural tube than the ta 2 [71]. While the ta 2 phenocopies craniofacial phenotypes associated with Oral-facial-digital syndrome subtype 14 (OFD14) [47,[95][96][97], the ta 3 presents with craniofacial phenotypes associated with Joubert syndrome including hypertelorism and hypoplastic jaws [98][99][100][101][102]. While the ta 2 and ta 3 GI tracts are both significantly shorter than control embryos, the intestinal ENS phenotypes are divergent from each other as the ta 2 hindgut has an increased number of ENCCs whereas ta 3 guts have reduced numbers of ENCCs [103,104].…”
Section: Discussionmentioning
confidence: 99%
“…For example, Hh signaling is required to properly pattern the dorsalventral axis of the somite that subsequently allows for differentiation into the dermatome (presumptive skin), myotome (presumptive muscle), and the sclerotome (presumptive vertebrae) [107][108][109][110]. Interestingly, previous studies reported that the ta 2 embryo presents with mispatterned muscles and a shortened vertebral column [42,48] and human patients that present with OFD14 possess musculoskeletal anomalies [96,97]. Future work with the ta 2 embryo will assess if and how these particular phenotypes arise due to perturbations in cilia-dependent Hh signaling.…”
Section: Discussionmentioning
confidence: 99%
“…79 We also observed dysregulation of several known ciliopathy genes, Jbts17, 80 Cep164, 81 Cep250, 82 Sclt1, 83 Ift140, 84 and C2cd3. 85,86 Additionally, Dzip1l, which is associated with an ARPKD-like phenotype in humans and mice by altering PC1/PC2 ciliary localization, 87 showed a significant increase in gene expression.…”
Section: Transcriptome Analysis Reveals a Dysregulated Ciliary Comparmentioning
confidence: 99%